2023
DOI: 10.1186/s12974-023-02912-9
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling identifies novel inflammation-related plasma proteins associated with ischemic stroke outcome

Annelie Angerfors,
Cecilia Brännmark,
Cecilia Lagging
et al.

Abstract: Background The inflammatory response to cerebral ischemia is complex; however, most clinical studies of stroke outcome focus on a few selected proteins. We, therefore, aimed to profile a broad range of inflammation-related proteins to: identify proteins associated with ischemic stroke outcome that are independent of established clinical predictors; identify proteins subsets for outcome prediction; and perform sex and etiological subtype stratified analyses. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In addition, we constructed and verified an IS diagnostic model consisting of six biomarkers, i.e., the abovementioned four proteins and two other immune response-related proteins: MASP1, CLEC4D, PIK3AP1, STC1, PTH1R, and HCLS1. The model demonstrated comparable or superior accuracy to IS models utilizing routine clinical hematology and biochemical characteristics, 43 inflammation-associated proteins, 44 or noncoding RNAs 45 in the bloodstream. However, it is important to note that our study focused solely on elucidating protein alterations at the immune level.…”
Section: ■ Discussionmentioning
confidence: 97%
“…In addition, we constructed and verified an IS diagnostic model consisting of six biomarkers, i.e., the abovementioned four proteins and two other immune response-related proteins: MASP1, CLEC4D, PIK3AP1, STC1, PTH1R, and HCLS1. The model demonstrated comparable or superior accuracy to IS models utilizing routine clinical hematology and biochemical characteristics, 43 inflammation-associated proteins, 44 or noncoding RNAs 45 in the bloodstream. However, it is important to note that our study focused solely on elucidating protein alterations at the immune level.…”
Section: ■ Discussionmentioning
confidence: 97%
“…PEA technology enables simultaneous measurement of a large number of proteins using minute amount of sample [7,10]. Studies using this approach have demonstrated its clinical utility in identifying important biomarkers for various diseases, including cancer, long COVID, ischemic stroke, and early pregnancy bleeding [10][11][12][13][14][15]. In this study, we used PEA to screen sera from pregnant, malaria-exposed women to identify differentially expressed proteins.…”
Section: Introductionmentioning
confidence: 99%